Nigmat Hakim in the dastan “Idegey” study - Zayneeva G.N. (Золотоордынское обозрение)
The purpose of this research is a scientific study of the text of the manuscript of Nigmat Hakim “On Dastan ‘Idegey’” and its introduction into scientific circulation. Research materials: A previously unpublished scientific work by the famous folklorist and linguist, Nigmat Hakim, entitled “On Dastan ‘Idegey’”, preserved in a manuscript in the fund No. 52 of the archive of the Center for Written Heritage of the G.Ibragimov Institute of Language, Literature and Art at the Tatarstan Academy of Sciences. This fund is valuable because there are various materials about the dastan “Idegey” and its versions. The scientific novelty of the study lies in the fact that the work of Nigmat Hakim is being studied in full for the first time. Based on this archival source, the manuscript, the reader is presented with a comprehensive scientific view of the dastan “Idegey”. When writing his study, N. Hakim refers to the works of famous scientists and orientalists, based on information from various written sources, quoting them as evidence of one aspect or another of the dastan in question. The results of the study: Most of the variants of the Tatar dastan “Idegey” have been preserved in manuscripts on Arabic graphics. One of the complete versions of the epic is the version of Sitdyk baba Zainetdinov, recorded by Nigmat Hakim in 1919. The text is scrupulously researched regarding the textual aspects: accurate reproduction of the source text, its authenticity, accessibility to the reader-researcher, commentary on the text, etc. The manuscript, “On Dastan ‘Idegey’”, consists of 13 chapters-sections, each of which is devoted to a particular issue of dastan research: the prerequisites for the emergence, preservation, variability, storytelling talents of the main characters, etc. There is a need to include the text of this manuscript within modern scientific circulation. It is one of the most valuable materials existing in source studies.